2009
DOI: 10.1155/2009/308596
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Suppresses the Formation of Osteoclasts by Increasing OPG Production via an Autocrine Mechanism Involving Celecoxib-Related Prostaglandins in Chondrocytes

Abstract: Elevated interleukin (IL)-1 concentrations in synovial fluid have been implicated in joint bone and cartilage destruction. Previously, we showed that IL-1β stimulated the expression of prostaglandin (PG) receptor EP4 via increased PGE2 production. However, the effect of IL-1β on osteoclast formation via chondrocytes is unclear. Therefore, we examined the effect of IL-1β and/or celecoxib on the expression of macrophage colony-stimulating factor (M-CSF), receptor activator of NF-κB ligand (RANKL), and osteoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…It has also been shown that IL-1β suppresses osteoclast formation by increasing osteoprotegerin 13) , and these phenomena result in increased prostaglandin E 2 production 14) .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that IL-1β suppresses osteoclast formation by increasing osteoprotegerin 13) , and these phenomena result in increased prostaglandin E 2 production 14) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Namba et al (22) reported that IL-6 and sIL-6r suppress differentiation of chondrocytes and induce expression of cartilage matrix proteins. On the other hand, Watanabe et al (15) reported that IL-1β suppressed the formation of osteoclasts by increasing OPG production via an autocrine mechanism involving the production of celecoxib-related prostaglandins, primarily PGE 2 , by chondrocytes. Thus, the present study focused on osteoclastic differentiation mediated by RANK/RANKL/OPG, through which chondrocytes communicate with osteoclast precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IL-6 is closely associated (9)(10)(11)(12). RANKL is highly expressed on osteoblasts/stroma cells and on the primitive mesenchymal cells surrounding the cartilaginous anlagen, ie, proliferating and hypertrophying chondrocytes (13)(14)(15). Osteoclast precursors recognize RANKL via RANK expressed on their cell surfaces and differentiate into mononuclear perfusion osteoclasts (POCs) in the presence of M-CSF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations